TEKNIK PEMBELAJARAN KOLABORATIF UNTUK MEMANDIRIKAN CALON JAMAAH HAJI PADA KELOMPOK BIMBINGAN HAJI MASJID ISTIQAMAH UNGGARAN - Muh Saerozi (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2014)
This quantitative research is intended as part of alternative solution for the Hajj at Masjid Istiqomah Ungaran in 2013. The research is focused on the technique on how to make the Hajj tobe self-reliance. Observation and interview are the technique on collecting the data through inductive approach. The finding shows (1) being self-reliance for the Hajj on religious activities and travel are not individual but collective; (2) improving one self-reliance not only require one but also collaborative teaching technique. (3)this collaborative technique will be effective when there is a support from the participant with different educational backgroundand the organizer who knows the participant as an adult.